Temperature Dependence of Hall Mobility AndCarrier Concentration of pb0.55S0.45 Films (Baghdad Science Journal, 2009)
Measurements of Hall effect properties at different of annealing temperature have been made on polycrystalline Pb0.55S0.45 films were prepared at room temperature by thermal evaporation technique under high vacuum 4*10-5 torr . The thickness of the film was 2?m .The carrier concentration (n) was observed to decrease with increasing the annealing temperature. The Hall measurements showed that the charge carriers are electrons (i.e n-type conduction). From the observed dependence on the temperature, it is found that the Hall mobility (µH), drift velocity ( d) carrier life time ( ), mean free path (?) were increased with increasing annealing temperature